Comparative study between Blair’s procedure of ankle fusion and arthroscopic ankle arthrodesis - Krishna, Daya; Upadhyay, Gunjan; Kumar, Alok; Singh Rawat, Chandra Mohan (International Journal of Research in Orthopaedics, 2021)
Background: Our objective was to perform a comparative study in terms of functional outcome of Blair’s procedure of ankle fusion versus arthroscopic methods of ankle fusion. Methods: 25 patients that underwent arthroscopic ankle arthrodesis versus Blair’s procedure of ankle fusion were taken for study at government medical college, Srinagar (VCSGGIMS and R) from the duration 2015-2021. Clinical assessment was done foot and ankle disability index and visual analog scale score for pain. Radiological assessment was done by serial X-rays. Regular follow-ups were taken till one year. Results: Both modalities proved to be equally effective in terms of patient’s functional outcome. Our analysis showed that Blair’s procedure ankle fusion was associated with a lower fusion rate (OR 0.26, 95% CI 0.13-0.52, p=0.0002), longer tourniquet time (MD 16.49, 95% CI 9.46-23.41, p<0.00001), and longer length of stay (MD 1.60,95% CI 1.10-2.10, p<0.00001) compared to arthroscopic ankle fusion; however, there was no significant difference between two groups in terms of infection rate (OR 2.41, 95% CI 0.76-7.64, p=0.14), overall complication rate (OR: 1.54, 95% CI 0.80-2.96, p=0.20), and operation time (MD 4.09, 95% CI 2.4910.66, p=0.22). Conclusions: We found no significant difference between two groups in terms of infection rate, overall complication rate, and operation time. Further high quality randomized controlled trials that are adequately powered are required.